Oat functionality in forage mixtures - Pacucci, G; Troccoli, C; Leoni, B (MTT, 2004)
In the rainfed arable land of the Mediterranean basin mixtures of oat and common vetch are planted for haymaking (Caballero et al. 1995, Assefa & Ledin 2001), and to improve the nutritive value of the forage (Thomson et al. 1990). The objective of this research was to evaluate the influence of different oat : vetch seeding rates on forage yield and quality. Field experiments were conducted under rainfed conditions in 1996-97 and 1997-98 growing seasons at Policoro, Southern Italy. The oat (O) and vetch (V) monocrops were compared with three O:V (70:30, 50:50; 30:70) seeding rates. Relative yields (RY) were calculated and the RY Total (RYT) was used as criterion for mi-xed stand advantage. N-total was determined to measure the forage quality. The seasons were different in total rainfall that contributed greatly to the results. Mean forage production (DMY) of mixtures was not significantly affected by increasing seeding rate of oat over the range used. Seeding rates of O did not influence botanical composition of mixtures. Decreasing O seed proportions, O mean contribution to DMY dropped by 20%, RY of O de-creased by 30%, and RY of V increased by 185%. For mixtures with 30% for oat, RYT exceeded unity suggesting a mixed stand advantage at lower oat seeding proportion. Forage quality was not significantly influenced by studied mixture rates. In conclusion, the net effect of oat in the mixture was to increasing competition as oat density increased. Assefa, G. & Ledin, I. 2001. Animal Feed Science and Technology 92: 95- 111; Caballero et al. 1995. Field Crops Research 41:135-140; Thomson et al. 1990. Experimental Agriculture 26: 49-56.
Keywords: Ka; oat; vetch; seed ratio; forage mixtures; Mediterranean basin